(untitled) (Research, Society and Development, 2022)
The use of technologies in communication and health have relevant changes in the care of the population, acting in a transforming way, respecting the principles of equity, cultures, regionalities, motor and psychic abilities. The objective was to identify, through updated literature, the importance of using information and communication technologies in the care of pregnant women. This is an integrative review of the literature of studies, involving scientific publications on the influence of educational technologies in the biopsychosocial context of pregnant and postpartum women. A total of 45 articles were found, of which a careful and floating reading was carried out and of these, four fit the research, presenting an acceptable level of evidence. The studies brought broad and different approaches in research on the influence of educational technologies in the biopsychosocial context of pregnant and postpartum women, from the titles to the methodological approach. The four studies were divided into two categories: 1) Lack of training of health professionals for the management of educational technologies. 2) Influence of the correct use of educational technologies, based on the title and subject addressed, so that they could be better explored. In this study, the importance of using educational technologies as a form of health promotion was highlighted.